Cultural Appropriation of Polynesian Portrayed In Moana Movie - Nurul Fatha; Maryam Adam; Rudianto A. Manaku; Sesar Tangkilisan (NOTION: Journal of Linguistics, Literature, and Culture, 2021)
This research aims to identify and describe cultural appropriation that were found in Moana. Cultural appropriation is one of the negative actions that can harm one culture. This action generally occurs due to a lack of understanding and appreciation of a culture. Based on Rogers[6] cultural appropriation as the use of a culture's symbols, artifacts, genres, rituals, or technologies by members of another culture, is inescapable when cultures come into contact, including virtual or representational contact. Rogers also divided cultural appropriation into four types, there are cultural exchange, cultural dominance, cultural exploitation, and transculturation. Based on Rogers theory above, cultural appropriation that were found in Moana is cultural exploitation. This research was used Qualitative descriptive method. The source data of this research are from “Moana” by Ron Clements and John Musker. This movie was released in 2016 with 113 minutes duration. This analysis shows there are four points of cultural appropriation that were found in “Moana”. Firstly, depiction figure of “Maui”, a demigod figure illustrated very different from the original form in the movie Moana. Secondly, depiction of Kakamora people. Thirdly, depiction of the cliché coconuts. Fourthly, Disney removing Maui’s family out of the tale. This leads to deviations in views towards the representatives of the population and Polynesian beliefs.